LINC00261 and the adjacent gene FOXA2 are epithelial markers and are suppressed during lung cancer tumorigenesis and progression - Dhamija, Sonam; Becker, Andrea Claudia; Sharma, Yogita; Myacheva, Ksenia; Seiler, Jeanette; Diederichs, Sven (Non-Coding RNA, 2019)
Lung cancer continues to be the leading cause of cancer-related deaths worldwide, with little improvement in patient survival rates in the past decade. Long non-coding RNAs (lncRNAs) are gaining importance as possible biomarkers with prognostic potential. By large-scale data mining, we identified LINC00261 as a lncRNA which was significantly downregulated in lung cancer. Low expression of LINC00261 was associated with recurrence and poor patient survival in lung adenocarcinoma. Moreover, the gene pair of LINC00261 and its neighbor FOXA2 were significantly co-regulated. LINC00261 as well as FOXA2 negatively correlated with markers for epithelial-to-mesenchymal transition (EMT) and were suppressed by the EMT inducer TGFβ. Hierarchical clustering of gene expression data from lung cancer cell lines could further verify the association of high LINC00261/FOXA2 expression to an epithelial gene signature. Furthermore, higher expression of the LINC00261/FOXA2 locus was associated with lung cancer cell lines with lower migratory capacity. All these data establish LINC00261 and FOXA2 as an epithelial-specific marker pair, downregulated during EMT and lung cancer progression, and associated with lower cell migration potential in lung cancer cells.